Ratio Legis Policy to Increase Women's Representation Through the Implementation of a Minimum Quota of 30% for Women in Nominations for DPR and DPRD Members - Bagus, Moh; Nurmila Sari, Helga (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2025)
Women as representatives in the strategic political making of decisions. Among the efforts made by the government to increase women's representation was setting a minimum threshold for female candidacy in the legislative and legislative elections. The policy referred to is set forth in Article 245 of Law Number 7 of 2017 concerning Elections. This research uses normative legal research methods with legislative and conceptual approaches. The provision regarding the minimum limit of 30% of women's candidacy is the implementation of constitutional rights, which is regulated in Article 28H Paragraph (2) of the 1945 Indonesian Constitution. The representation of women in the legislature was entrusted as a form of balancing and alignment of patriarchal and dominative elements in strategic policymaking. There are five ratios of an increase in female representation policy, including the existence of women in political decision-making is a counterweight to the patriarchal elements; women's brain variables are wider than men's so as to impact the different responses to an accepted issue; policy correlation with zipper system theory; policy correlation with critical mass theory; and the form of exercise of rights and duties owned by women as right holders and men as duty holders. The increase of female participation in representation can be achieved through political recruitment and the establishment of a political party-wing organization.